2020
DOI: 10.1039/d0fo01746a
|View full text |Cite
|
Sign up to set email alerts
|

Edible mushrooms as a novel protein source for functional foods

Abstract: Fast demographic growth has led to an increasing interest in low-cost alternative protein sources to meet population needs. Consequently, the attention of many researchers has focused on finding under-exploited sources...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 96 publications
2
85
0
2
Order By: Relevance
“…These peptides, known as bioactive peptides, have positive health related effects, such as antioxidant activity and also others, e.g. they have been characterized as antimicrobial, hypocholesterolemic, antihypertensive and immunomodulatory (González et al, 2020;Li-Chan, 2015). On the other hand, as many of these compounds are sensitive to extreme temperatures, light or oxygen exposure, processing conditions can affect their antioxidant capacity (Ioannou, Chekir & Ghoul, 2020).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…These peptides, known as bioactive peptides, have positive health related effects, such as antioxidant activity and also others, e.g. they have been characterized as antimicrobial, hypocholesterolemic, antihypertensive and immunomodulatory (González et al, 2020;Li-Chan, 2015). On the other hand, as many of these compounds are sensitive to extreme temperatures, light or oxygen exposure, processing conditions can affect their antioxidant capacity (Ioannou, Chekir & Ghoul, 2020).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Sciarini, et al [46] found that the addition of oat bran fibre and resistant starch into a gluten-free bread (rice flour) increased the percentage of protein hydrolysis and suggested that this was achieved by disrupting the crumb structure. Fibre can also act as a physical barrier to some enzymes and delay the hydrolysis of proteins or polypeptides [18]. The solubility and digestion of protein could also be related to the molecular weight of the protein, and the 15% T. fuciformis biscuit had a low Mw of protein fraction and a higher soluble protein content compared to the control.…”
Section: Protein Profile and Soluble Protein Content After Digestionmentioning
confidence: 99%
“…It is of great interest to incorporate mushrooms into cereal products to improve the nutritional quality and functionalities of products in recent studies [15][16][17][18]. However, mushroom dietary fibre might negatively affect the bioaccessibility of the phenolic compounds and the digestion of other nutrients when they are enriched in products.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal polysaccharides are known to possess great antioxidant activities, as have been shown in Lentinus edodes [ 112 ], Grifola forndosa [ 113 ] and Leucopaxillus giganteus [ 114 ]. The functional and nutritive properties of fungi as dietary protein sources have also been discussed and reviewed elsewhere [ 115 ]. While edible mushrooms are generally regarded as containing a high level of proteins and carbohydrates, further investigation on the studies performed for the last 10 years indicates that the fungal nutritive characteristics vary depending on the genera of the fungi, wild or cultivated, the geographical location, and the cultivation media ( Table 2 ).…”
Section: Fungi As Protein and Carbohydrate Sourcementioning
confidence: 99%